Shaping Balanced Minds: Exploring the Integration of Religious Moderation in Indonesian Elementary Education - Muchamad Fauyan; Anwar Efendi; Sugeng Bayu Wahyono; Sugito Sugito; Nur Kholis (Jurnal Ilmiah Peuradeun, 2026)
Religious moderation has become a strategic agenda in Indonesian education to strengthen social cohesion in pluralistic societies. At the primary education level, studies on religious moderation remain fragmented and require integrative synthesis. This study examines how religious moderation education is implemented in Indonesian elementary schools and Madrasah Ibtidaiyah (SD/MI) through a Systematic Literature Review retrieved from Google Scholar, Scopus, ScienceDirect, and Elicit.ai. The analysis focuses on conceptualization, pedagogical implementation, and reported challenges and impacts. The findings indicate that religious moderation education at the SD/MI level is predominantly implemented through integrative and implicit practices rather than as a standalone curricular subject. Moderation values—such as justice, tolerance, inclusivity, and social harmony—are embedded across curricula, learning materials, pedagogical strategies, and school culture, with teachers functioning as key mediators of value internalization. While moderation-oriented education contributes to more inclusive school climates and positive student attitudes toward diversity, its implementation remains uneven due to limited teacher conceptual clarity, competing academic demands, and the growing influence of digital environments. This study contributes by articulating embedded moderation pedagogy as a conceptual framework for understanding religious moderation education in early schooling. The findings provide a concise reference for advancing research, policy development, and educational practice in religious and character education within pluralistic contexts.